CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA DAN KINERJA KEUANGAN - Lusye Corvanty Kumaat (Jurnal Keuangan dan Perbankan, 2013)
The research was aimed to examine the effect of corporate governance and ownership structure on profitmanagement and financial performance. Corporate governance mechanisms that were used in this researchwere managerial ownership, independent commissioner and audit committee. Ownership structure that wasused was concentrated ownership structure. Research was conducted on the manufacturing companies thatwere listed at Indonesia Stock Exchange in period of 2007-2011. Sampling technique was purposive sampling.Hypothesis testing tool was multiple regression. Earning management in this research was measuredusing Modified Jones Models, while financial performance was measured by cash flow return on assets (CFROA).Result of research indicated that managerial ownership, independent commissioner, and ownership structurewas positively influencing profit management. Independent commissioner and ownership structure positivelyinfluenced financial performance, while managerial ownership negatively influenced financial performance.Audit committee was not influencing earning management and financial performance, and earning managementwas not proved as influencing financial performance.